To Correlate the Serum Levels of Adiponectin with Fasting and Random Blood Sugars in Diabetes Mellitus and Healthy Individuals (Medical Forum Monthly, 2024)
Objectives: To correlate the serum levels of adiponectin with fasting and random blood sugars in diabetic and healthy individuals.Study Design: Comparative cross sectional study.Place and Duration of Study: The study was carried out at the Department of physiology B.M.S.I. J.PM.C. in collaboration with Abassi Shaheed Hospital Karachi from August 2007 to July 2009.Materials and Methods: This study included total 100 subjects, 50 subjects with known case of Diabetes Mellitus and 50 normal healthy age and gender matched controlsResults: A significant negative correlation (r = - 0.65 and r = - 0.80) (P<0.01) was found between fasting and random blood sugars and serum adiponectin in Diabetics.Conclusion: This suggests that higher levels of serum adiponectin may be protective against the development of Diabetes Mellitus